SPRAYING NANO CHITOSAN LOADED WITH NPK, NETTEL AND GREEN TEA EXTRACTS AS A TOOL FOR IMPROVEMENT POTATO PRODUCTIVITY - Z. R. J. AL- Malikshah; Z. R. J. AL- Malikshah; I. J. Abdulrasool (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to evaluate the effect of spraying nano chitosan loaded with NPK fertilizer and nettle leaf and green tea extracts on the growth and productivity of potato for the spring and fall seasons of 2021.It was conducted at private farm in Wasit Governorate, Iraq, as a factorial experiment (5 × 5) within randomized complete block design using three replicates. The first factor included spraying with four concentrations of chitosan nanoparticles loaded with NPK fertilizer 0, 10. 15 and 20% in addition to chemical fertilization treatment, the second factor was spraying nettle leaf extract 25 and 35 gL-1 and green tea extract with 2 and 4 g.L-1, in addition to the control treatment, spraying with distilled water only. The results showed a significant superiority of the interaction between spraying with Nano chitosan loaded with NPK at a concentration of 15% and spraying green tea extract at a concentration of 4 g L-1 significantly in producing the highest plant height 62.77 and 60.86 cm, number of main stems of the plant 4.45 and 4.36 stem for the both seasons respectively and mean of tuber weight (111.0 g tuber-1) for the spring season which increased the productivity of tuber yield (56.3 and 51.6 in ton ha-1 for both seasons, respectively).